ENGLISH PRONUNCIATION CHALLENGES FACED BY BS ENGLISH 7th SEMESTER STUDENTS - Rabeea Tariq; Ayesha Bukhari; Usama Manzoor (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the challenges faced by students of B’s English 7th semester at the University of Kotli in pronunciation. These challenges include incorrect pronunciation, struggles with silent letters, mispronunciation of words borrowed from other languages into English, and difficulty distinguishing between similar sounds. The study aims to understand how pronunciation impacts overall communication skills. A questionnaire was designed and administered to a sample of 15 students from the English department enrolled in the 7th semester of B’s English. Data was collected through a questionnaire consisting of close-ended questions. The findings indicate that pronunciation plays a crucial role in communication, and incorrect pronunciation can negatively impact students’ confidence in speaking English at the undergraduate level. Recommendations for future research would include emphasizing the importance of consistent practice in improving pronunciation. Students should engage in regular English-speaking practice to enhance their pronunciation skills. Additionally, they should practice English sounds by utilizing their own speech organs.